GEJALA CAMPUR KODE CERAMAH K.H. ANWAR ZAHID DI YOU TUBE ANZHA CHANEL DALAM RANGKA BERSHOLAWAT DAN PENGAJIAN AKBAR BALONG BLORA - Sutardi Sutardi; Ernaningsih Ernaningsih (Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to uncover the issues of code mixing in the speeches of K.H. Anwar Zahid on YouTube during religious lectures and grand recitations at Balong Blora. The code mixing involves the incorporation of Indonesian language into English, Arabic, and Javanese. The study on K.H. Anwar Zahid utilizes a qualitative descriptive method with a Sociolinguistic approach. The data for this research includes various forms of code mixing, such as words and phrases. The manifestations of code mixing occur in speeches delivered in Indonesian, English, and Javanese during religious lectures. Data are obtained from video documentation on the YouTube channel, and the data collection technique involves documentation. The data analysis technique employs the interactive model by Miles Huberman. The research findings describe the forms of code mixing, including words and phrases. The code mixing is observed in speeches delivered in Indonesian, English, Arabic, and Javanese during religious lectures. The research also provides a description of the factors contributing to the occurrence of code mixing.